2023
DOI: 10.1186/s40644-023-00528-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor size measurements of pancreatic cancer with neoadjuvant therapy based on RECIST guidelines: is MRI as effective as CT?

Abstract: Objectives To compare tumor size measurements using CT and MRI in pancreatic cancer (PC) patients with neoadjuvant therapy (NAT). Methods This study included 125 histologically confirmed PC patients who underwent NAT. The tumor sizes from CT and MRI before and after NAT were compared by using Bland–Altman analyses and intraclass correlation coefficients (ICCs). Variations in tumor size estimates between MRI and CT in relationship to different facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Similarly to MDCT, MRI utilizes time-contrast images to visualize the arterial and portal venous anatomy. Yang et al [88] showed that MRI and CT have similar performance in assessing PDAC tumor size before and after NAT. However, dynamic MRI is not commonly performed and should only be attempted by experienced centers due to difficulties in reproducibility and standardization [89].…”
Section: Resectability After Nat/nacrtmentioning
confidence: 99%
“…Similarly to MDCT, MRI utilizes time-contrast images to visualize the arterial and portal venous anatomy. Yang et al [88] showed that MRI and CT have similar performance in assessing PDAC tumor size before and after NAT. However, dynamic MRI is not commonly performed and should only be attempted by experienced centers due to difficulties in reproducibility and standardization [89].…”
Section: Resectability After Nat/nacrtmentioning
confidence: 99%